Minimum cost design of ring and stringer stiffened cylindrical shells - Liszkai, Tamás; Farkas, József (Computer Assisted Methods in Engineering and Science, 2023)
In this paper the optimum design of bent cylindrical shells with welded ring or stringer stiffeners are treated. The objective function is the cost of the structure and the constraints are related to overall and local stability. The problem is solved by MathCad 7.plus software and presented also graphically for ring stiffened cylinders and by CFSQP optimization software for stringer stiffened cylinders.